Protein Drugs - Linh, Nguyen Hue; Hue, Pham Thi Minh; Binh, Nguyen Thi Thanh; Thanh Tung, Bui; Yen, Nguyen Thi Hai; Hai, Nguyen Thanh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2022)
Abs tract: To serve health care, up to now, sciences have successfully developed many drugs with different effects. In general, in terms of chemical structure and effect characteristics, medicine can be classified into groups including inorganic drugs, small-molecule organic drugs, protein drugs (macromolecules), and recently a new group of drugs has been formed, separate from the protein drug class, which is the RNA drugs. In terms of pharmacological effects, in general, the mechanisms of protein drugs and small-molecule organic drugs do not differ too much because they all act at a particular stage related to pathological manifestations. Protein drugs in the process of development have gone through many different stages, with different origins, from extraction and isolation from living tissues at an early stage to biosynthesis by recombinant technology and other modern biotechnology methods. To date, most of the proteins used in medicine have been produced through recombinant pathways, possibly through different semisynthetic steps to give the molecules more superior drug properties. Therefore, the group of protein drugs has an additional new name, biopharmaceuticals, to indicate their synthetic origin by biological methods. The research, development, and application of protein drugs into clinical practice are of great significance, helping to enhance the ability of medicine to control and treat many difficult-to-treat diseases today, bringing many opportunities to have good health for people. Keywords: Protein drugs, RNA drugs, Biopharmaceuticals, Inorganic drugs, Small-molecule organic drugs, Drug development, Cytokine, Enzyme, Hormone peptide, Stem cell, Recombinant technology, Biosimilar. *